Ezekiel the man and his message - Ellison, Henry Leopold, 1903- (Exeter, UK Paternoster, 1956)
Includes bibliographical references.
Copy 1 donated by My V. Poke, student, 1960. Brethren writer.
Keywords: Bible. O.T. Ezekiel -- commentaries